2015
DOI: 10.1002/elps.201500198
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth proteomics approach of secretome to identify novel biomarker for sepsis in LPS‐stimulated endothelial cells

Abstract: Sepsis and septic shock, which are conditions triggered by infection, occur with high incidence in emergency departments and are among the most common causes of death in hospitalized patients worldwide. Therefore, the identification of sepsis biomarkers for the rapid diagnosis is a major goal for researchers in the field of critical care. Endothelial cells play a pivotal role in orchestrating the inflammatory response triggered by sepsis. In this study, we used proteomics to investigate the secretome of EA.hy9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…Sepsis remains a common, expensive, and deadly problem throughout the world 21 . To explore the influencing factors such as miR-15a in the progression of sepsis, the rat sepsis model (sepsis group and septic shock group) was established in current study.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis remains a common, expensive, and deadly problem throughout the world 21 . To explore the influencing factors such as miR-15a in the progression of sepsis, the rat sepsis model (sepsis group and septic shock group) was established in current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the method used in this study simulates the pathophysiology of sepsis rather than cardiac remodeling, many inflammatory pathways are also activated in cardiac remodeling. Interestingly, endotoxins upregulate secretion of some of the proteins present in our index list; e.g., thrombospondin-1 secretion increases 1.2-fold, follistatin-related protein 1 secretion increases 1.2-fold, and connective tissue growth factor increases 1.8-fold (Kwon et al, 2015 ; Table 4 ). In a separate mass-spectrometry study in the same EC line it was shown that atorvastatin decreases protein secretion of thrombospondin-1, thrombospondin-2, and connective tissue growth factor (Brioschi et al, 2013 ).…”
Section: Microvascular Endothelial Cells Secrete Proteins That Modulamentioning
confidence: 98%
“…Therefore, we searched literature for mass-spectrometry data on the secretome of ECs. Specific data on cardiac microvascular ECs are not available, but mass spectrometry data have been published on the secretome of HUVECs (Tunica et al, 2009 ), endothelial progenitor cells (Hemmen et al, 2011 ), and EA.hy926 ECs (HUVEC hybridoma cell line) (Brioschi et al, 2013 ; Kwon et al, 2015 ).…”
Section: Microvascular Endothelial Cells Secrete Proteins That Modulamentioning
confidence: 99%
See 1 more Smart Citation
“…Although their data are comparable to PCT measurement for sepsis diagnosis, they showed that their metabolomics approach was a better predictor of disease outcome. Kwon et al [26 ]used proteomics to analyze the secretome of endothelial cells following LPS stimulation and subsequently identified moesin and 19 new sepsis biomarker candidates. Nakada et al [27 ]used bioinformatics approach to identify a single nucleotide polymorphism on the SVEP1 gene that is associated with increased sepsis mortality.…”
Section: Development Of Conceptmentioning
confidence: 99%